If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = e + 2.7 Reorder the terms: 10 = 2.7 + e Solving 10 = 2.7 + e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-1e' to each side of the equation. 10 + -1e = 2.7 + e + -1e Combine like terms: e + -1e = 0 10 + -1e = 2.7 + 0 10 + -1e = 2.7 Add '-10' to each side of the equation. 10 + -10 + -1e = 2.7 + -10 Combine like terms: 10 + -10 = 0 0 + -1e = 2.7 + -10 -1e = 2.7 + -10 Combine like terms: 2.7 + -10 = -7.3 -1e = -7.3 Divide each side by '-1'. e = 7.3 Simplifying e = 7.3
| 2x+5x+8= | | 3a-7a=8 | | -3y=18-9(-2) | | 3a-7whena=8 | | -3y=18-9(0) | | 6.2*3= | | -3y=18-9(2) | | 184=23p | | 2(7)=(x+9)2/3 | | 2(-6+4x)=-84 | | 7a*3a*10B= | | y=2*0+(-2) | | 2(7)=(x+9)2 | | 173-5x=40x+18 | | 7t-4*2t+3t*4/2 | | 10+p=3 | | 6-2(4x)+7=0 | | 5(-2)=y+6 | | 7a*3a= | | 5(0)=y+6 | | 4-9p=49 | | 3/4+5/3 | | 5(2)=y+6 | | 9*n=53 | | 2y-6.2+y=8.8 | | -4+8X=5+2X | | 2(m+5)=28 | | 12+(21-6)/3 | | (4y+3)-(-3y-6)=-2 | | -2(6)+9=-(9)-3 | | -2(-12)+9=-(0)-3 | | 4(x-6)+2=6x-6 |